2016
DOI: 10.1177/0883073816664836
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Whole Exome Sequencing for Genetic Diagnosis of Previously Undiagnosed Pediatric Neurology Patients

Abstract: Whole exome sequencing enables scanning a large number of genes for relatively low costs. The authors investigate its use for previously undiagnosed pediatric neurological patients. This retrospective cohort study performed whole exome sequencing on 57 patients of "Magen" neurogenetic clinics, with unknown diagnoses despite previous workup. The authors report on clinical features, causative genes, and treatment modifications and provide an analysis of whole exome sequencing utility per primary clinical feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
42
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 27 publications
6
42
3
1
Order By: Relevance
“…These observations differ from ours, where 35.1% of the definitely diagnosed patients emerged in a recessive mode (Fig. 1d), which is in good agreement with previous diagnostic WES studies [10, 35, 36].…”
Section: Discussionsupporting
confidence: 87%
“…These observations differ from ours, where 35.1% of the definitely diagnosed patients emerged in a recessive mode (Fig. 1d), which is in good agreement with previous diagnostic WES studies [10, 35, 36].…”
Section: Discussionsupporting
confidence: 87%
“…A change of patient medication, either initiation of a new treatment or halting of an existing one, was specifically reported in 22 studies. 8,[15][16][17][18]20,22,23,[26][27][28][29][30][31][32][33][34][35][36][37][38][39] For example, Anazi et al reported a patient with ID who was homozygous for a truncating pathogenic variant in SLC39A14 that causes a potentially treatable form of hypermanganesemia, who was started on chelation therapy, resulting in improved manganese levels. 17 In a case series of patients with presumed neurogenetic disorders and DD/ID from Argentina, 10% (4/ 40) underwent a trial of new medication following ES, including a trial of L-Dopa in a patient with paraplegia and ID who had pathogenic variants in SPG11 and a trial of acetazolamide and fampridine in a patient with a pathogenic variant in KCNA2.…”
Section: Medication and Dietary Managementmentioning
confidence: 99%
“…39 Alterations to a patient's existing diet were mentioned in nine studies. 8,23,26,27,30,31,33,40,41 In a case series of 43 French patients with dysmorphic features and neurodevelopmental disorders including severe to profound ID, a patient diagnosed with compound heterozygous pathogenic variants in ADCK3 was diagnosed with coenzyme Q10 deficiency. Coenzyme Q10 supplementation and a ketogenic diet were introduced following ES results.…”
Section: Medication and Dietary Managementmentioning
confidence: 99%
“…3,6 Note that these studies have already identified and excluded patients with the more common nucleotide repeat expansion diseases.…”
Section: Clinical Exome Sequencingmentioning
confidence: 99%
“…Simultaneous interrogation of multiple genes using clinical exome sequencing or a large multigene panel is increasingly reported as an efficient method for identifying a diagnosis in individuals with ataxia. [3][4][5] However, the most common causes of hereditary ataxia are due to nucleotide repeat expansions that would not be identified by these sequencing techniques.…”
mentioning
confidence: 99%